PENGARUH KOMPENSASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KOTA PALEMBANG - RM Rionaldi Bakrie; Riswan Jaenudin (Politeknik Negeri Ambon, 2025)
Introduction: This study analyzes the effect of compensation on employee productivity at the Environmental Agency of Palembang City. Methods: The sample included 70 employees from three categories: Civil Servants (PNS), Government Contract Employees (PPPK), and Honorary Staff. Data were collected through validated questionnaires (27 items for compensation, 20 items for productivity), in-depth interviews with 7 employees, and document analysis. Instrument validity and reliability were tested using product moment correlation (validity) and Cronbach’s alpha (reliability), with reliability coefficients exceeding 0.7 for both variables. Questionnaire results revealed 54.3% of respondents rated compensation as